Facility Management of Nigerian Universities: Case of University of Lagos, Lagos and the Bells University of Technology, Ota, Nigeria (International Journal of Built Environment and Sustainability, 2018)
Universities which are citadel of research and learning have many facilities that need to be well maintained in order to achieve the designed aim and sustain value of the institution. This necessitates the need for this study to examine facility management practice and the level of satisfaction of users of facility management in the study areas. The study populations are the students and staff of the institutions who are the users of the facilities. The sampling technique is systematic random sampling technique where respondents were selected from all the academic faculties, student’s hostels, and staff quarters which makes all categories of facilities users to be captured. The analysis was done using tables, 5-point Likert scale. The facility management services were categorized into hard and soft services. The modes of execution of the two were studied. It was gathered that some of the hard and soft services were outsourced while some are done in-house. The levels of satisfaction of the users on the hard and soft services were measured. It was gathered that soft services like move management have least ranking in the two universities and hard services like decoration and refurbishment have least ranking in the two universities. Recommendations were made on how the two universities can improve facility management services.
Keywords: Facility; Facility management; Soft Services; Hard Services; Universities